Non-invasive bladder function measures in healthy, asymptomatic female children and adolescents: A systematic review and meta-analysis. Issue 4 (August 2021) - Meister, Melanie R.; Zhou, Jincheng; Chu, Haitao; Coyne-Beasley, Tamera; Gahagan, Sheila; Yvette LaCoursiere, D.; Mueller, Elizabeth R.; Scal, Peter; Simon, Laura; Stapleton, Ann E.; Stoll, Carolyn R.T.; Sutcliffe, Siobhan; et al.
Summary: Background: Lower urinary tract symptoms (LUTS) are common in children and adolescents. Non-invasive tests evaluating bladder function are generally preferred over invasive tests, yet few studies have explored the range of normative values for these tests in healthy, asymptomatic children. Objective: To define normative reference ranges for non-invasive tests of bladder function in healthy, asymptomatic girls and adolescents. Study design: A comprehensive search strategy was performed in seven electronic databases through October 2019. English-language studies reporting data on voiding frequency, voided and postvoid residual volumes (PVR) and uroflowmetry results in healthy, asymptomatic girls (mean age ≥ 5 years) were included. Two independent reviewers performed study review, data extraction, and quality assessment. Overall mean estimates and 95% confidence intervals for each bladder function parameter were calculated using random effects models, and 95% normative reference values were estimated. Results: Ten studies met eligibility criteria for the meta-analysis (n = 2143 girls, age range: 3–18). Mean estimates of maximum voided volume and PVR were 233.4 ml (95% CI 204.3–262.6; n = 1 study) and 8.6 ml (95% CI 4.8–12.4; n = 2 studies) respectively. Pooled mean estimates for uroflowmetry parameters were: 21.5 ml/s (95% CI 20.5–2.5) for maximum flow rate (n = 6 studies), 12.5 ml/s (95% CI 11.2–13.8) for mean flow rate (n = 6 studies), 6.8 s (95% CI 4.4–9.3) for time to maximum flow (n = 3 studies), 15.7 s (95% CI 13.0–18.5) for flow time (n = 3 studies), and 198.7 ml (95% CI 154.2–234.2) for voided volume (n = 9 studies). No studies reported estimates of voiding frequency. Between-study heterogeneity was high (89.0–99.6%). Conclusions: Although we were able to calculate pooled mean estimates for several parameters, the small number of included studies and the wide age ranges of participants preclude generalization of reference values to all healthy girls. Further research is needed to determine normative reference values within specific age groups.